Short-term effects of bone meal powder on soil phosphorus availability, seed germination, and early growth parameters of Malabar Spinach (Basella alba) - Aishwa Roy; Protima Sarker (PLoS ONE, 2026)
There is a growing need to find alternatives to chemical fertilizers, particularly for Phosphorus supply. Chemical fertilizers contribute to environmental problems and natural phosphate resources are depleting. The main objective of the study was to examine the effect of bone meal powder (BMP) as an organic fertilizer on soil phosphorus availability, seed germination, and early growth performance of Malabar spinach ( Basella alba ). Two experiments were conducted: soil chemical analysis and pot experiment. Experiment 1 referred to highly saline soil-High Electrical Conductivity (EC) and Experiment 2 used non-saline- Low Electrical Conductivity (EC) soil. The treatments included: T1: High EC soil; only potting media; no BMP, T2: High EC soil amended with BMP, T3: Low EC soil; only potting media; no BMP, T4: Low EC Soil amended with BMP. All treatments were used to analyze the soil chemical properties, including soil pH, EC and Phosphorus. For the pot experiment, treatments (T3 and T4) were combined in a completely randomized design with three replicates and the data were collected on germination and early growth parameters of malabar spinach. Results revealed that the application of BMP increased soil pH, EC and notably improved phosphorus availability, compared to the control in both soils. However, BMP negatively affected germination and early growth variables in experimental soil 2. In spite of the great differences in shoot length were observed in the application of BMP, only minor differences were found in root lengths and fresh weight. The correlation analysis showed that mean germination time had negative relationships with growth parameters. The findings suggest that BMP may have potential as an inexpensive and eco-friendly fertilizer, although further large-scale field experiments are necessary to confirm its effectiveness. These results may inform researchers, stakeholders, and agricultural practitioners regarding the potential use of BMP.